On the current status of the Church schism in Abkhazia - V. Mukhanov (Международная аналитика)
The article examines the current status of the Church schism in Abkhazia, given his assessment and the background to the emergence. Analyzes the arragment of forces and positions of outside players in this issue, as well as the prospects for its resolution.